1995
DOI: 10.1177/088307389501000212
|View full text |Cite
|
Sign up to set email alerts
|

Brain Weight and Sudden Infant Death Syndrome

Abstract: Increased brain weights have been reported in the literature to occur among infants who have died from sudden infant death syndrome, suggesting that cerebral edema might play a role in the cause of death among these children. We have compared brain weights from children between the ages of 1 week and 1 year, autopsied between 1980 and 1992. One group consisted of 125 victims of sudden infant death syndrome and the other of 38 children who had died with a diagnosis other than the sudden infant death syndrome. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…Several groups have examined brain weight in SIDS [7][8][9][10][11][16][17][18][19][20]. The majority of these investigators have reported that the brain (either in isolation, or expressed as a ratio of brain weight : body weight) is heavier in SIDS than either a control population or published 'normal' data [7][8][9][10][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have examined brain weight in SIDS [7][8][9][10][11][16][17][18][19][20]. The majority of these investigators have reported that the brain (either in isolation, or expressed as a ratio of brain weight : body weight) is heavier in SIDS than either a control population or published 'normal' data [7][8][9][10][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Brain weight : body weight ratio Brain weight [7] 79 and reference data 79 Reference data -SIDS heavier [16] 261 and reference data 208 53 and reference data -SIDS heavier [17] 150 61 89 -SIDS heavier [8] 227 and reference data 227 Reference data No difference SIDS heavier [9] 163 and reference data 125 38…”
Section: Number Of Sids Cases Number Of Control Casesmentioning
confidence: 99%
“…When organ weights are measured as a function of body weight (not age) some studies show significant differences between cases of SIDS [77,78] and non-SIDS while others contradict these [79]. Reasons for the discrepancies between the studies relate to features of the control groups (presence of infection, gestational age, changes in infant nutritional status with socioeconomic development, and so on).…”
Section: Discussionmentioning
confidence: 99%
“…A previously published study demonstrated that one specific AQP4 variation (rs2075575) can be related to increased brain weights in SIDS infants, suggesting that this variation may predispose the development of cerebral edema (15). The association of an increased brain weight and SIDS, however, is controversial because some studies reported an increased brain weight in SIDS infants compared with gender-and agematched controls, whereas others could not confirm such a correlation (16)(17)(18)(19). Therefore, one might speculate that an increased brain weight is not a general indicator for SIDS but is only seen in combination with genetic or environmental risk factors (15,19).…”
mentioning
confidence: 85%